ASSESSMENT OF DIFFUSION GAMMA AND NEUTRON DOSE, FOR THE PURPOSE OF OPTIMIZING THE RADIATION PROTECTION IN TRIGA 2000 BATAN - Lovanantenaina Omega, RAKOTOVAO
The TRIGA 2000, located in Bandung Indonesia, is a research reactor installation which is currently operated at 1000 kW. As it is a nuclear installation, Gamma and neutron radiation exposure will contribute to occupational doses that will be received by operators and other radiation workers. To maintain the safety of radiation workers, assessment of gamma and neutron radiation is needed in the TRIGA 2000 reactor. A survey was carried out in the hall reactor using the RTD 30 and RadEye NL detectors to measure the gamma and neutron dose rate during the operation of the reactor area which is divided in 32 points. In addition to the direct measurement, calculations has been realized with simulation data dose using Monte Carlo MCNPX and PHITS to get the output of the dose in a limited distance and followed by the extrapolation using the TVL methods to complete the calculation of the dose rate. The study will focus on the assessment of the diffusion Gamma and neutron doses by doing the measurement and simulation data collect for the aim of the optimization of the Radiation protection policy in the reactor TRIGA 2000 Bandung. The results of the measurement are shown with graph in different power and the simulations are illustrate by graphical distribution dose of gamma and neutron using PHITS code output and extrapolation using TVL method to estimate the hall reactor dose. All simulation graph are designed using ANGEL software. The results from simulations will be compared with several points chosen from the 32 points of mapping area. A preventive technique to mitigate the exposure of the worker and publics is elaborated to optimize the Radiation protection program and suggestions are given regarding to the measurement and the simulation.